2021
DOI: 10.1002/rth2.12499
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence artifact correction in the thrombin generation assay: Necessity for correction algorithms in procoagulant samples

Abstract: Introduction The thrombin generation (TG) test is a global hemostasis assay sensitive to procoagulant conditions. However, some TG assays may underestimate elevated TG when the thrombin fluorogenic substrate is depleted or fluorescence is attenuated by the inner filter effect (IFE). Objectives We sought to elucidate the extent to which procoagulant conditions require correcting for fluorogenic substrate depletion and/or IFE. Methods We analyzed corrections for substrate depletion and IFE and their effect on TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A 96‐channel pipettor (Viaflo 96, Integra Biosciences) was used to activate the plasma mixture with calcium chloride (final concentration 10 mM). In parallel, matched plasma wells with CAT thrombin calibrator (Stago) were used to generate a cubic polynomial‐fitted curve for calibration of the TG curves (also known as thrombograms) as described in Chang et al 9 The corresponding fluorescent signal was recorded on a Synergy Neo2 at 37°C simultaneously at several combinations of Ex/Em wavelengths chosen to represent the settings used in published TG assays (Table 1). A monochromator bandwidth for Ex and Em wavelengths was set up at 10 nm for all tested settings.…”
Section: Methodsmentioning
confidence: 99%
“…A 96‐channel pipettor (Viaflo 96, Integra Biosciences) was used to activate the plasma mixture with calcium chloride (final concentration 10 mM). In parallel, matched plasma wells with CAT thrombin calibrator (Stago) were used to generate a cubic polynomial‐fitted curve for calibration of the TG curves (also known as thrombograms) as described in Chang et al 9 The corresponding fluorescent signal was recorded on a Synergy Neo2 at 37°C simultaneously at several combinations of Ex/Em wavelengths chosen to represent the settings used in published TG assays (Table 1). A monochromator bandwidth for Ex and Em wavelengths was set up at 10 nm for all tested settings.…”
Section: Methodsmentioning
confidence: 99%
“…We use thrombin as a model protease due to its central role in the coagulation cascade and its key role in clotting diseases. Also, its involvement in the homeostasis of the gut and central nervous system has been recently suggested, indicating its potential as a biomarker for other pathological conditions. Hence, biosensing assays to quantify thrombin’s activity are much needed in both fundamental biochemistry studies and in the future in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, our previous investigations suggested that the IFE and substrate consumption can be of little consequence for detection of elevated TG in normal plasma spiked with increasing levels of coagulation factors I, V, VIII, IX, X, and XI [ 5 ]. On the other hand, algorithmic CAT corrections for substrate consumption were helpful in moderate cases of elevated prothrombin [ 6 ] and antithrombin deficiency [ 7 ]. Yet, in more severe conditions of substantially elevated prothrombin or deficient antithrombin, CAT algorithm failed to produce TG curve parameters due to its inability to process substantially distorted fluorescence signals.…”
Section: Introductionmentioning
confidence: 99%
“…We employed three versions of the CAT correction algorithm (Fig. 1), commercial Thrombinoscope software (denoted here as TS software) [3], our in-house app for TG analysis written in LabTalk language for Origin statistical and graphical software (Origin; denoted as OR software) [5,6,10], as well as the publicly available software, labelled SH, developed by one of us (CL) as part of a project to improve reproducibility and transparency supported by the International Society for Thrombosis and Haemostasis (ISTH) Subcommittee on Fibrinolysis [11].…”
Section: Introductionmentioning
confidence: 99%